2015
DOI: 10.1097/mpg.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Surfactant Protein‐A Reduces Pathology in an Experimental Model of Necrotizing Enterocolitis

Abstract: OBJECTIVES Necrotizing enterocolitis (NEC) frequently results in significant morbidity and mortality in premature infants. Others reported that mice deficient in pulmonary surfactant protein-A (SP-A) born and raised in a nonhygienic environment succumb to significant gastrointestinal tract pathology, and enteral administration of purified SP-A significantly reduced mortality. We hypothesized that oral administration of purified SP-A can ameliorate pathology in an experimental model of neonatal NEC. METHODS E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…It is noteworthy that the clinical factors most often seen in association with NEC, including hypoxia, remote infection, and prematurity, are all associated with induced TLR4 expression in the intestine, suggesting a biologic explanation for these clinical observations. The principal findings that the LPS recognition molecule TLR4 is elevated in experimental and human NEC, and that it plays a key role in the pathogenesis of this disease, has been confirmed by a variety of investigators 40,41,42,43,44,45 .…”
Section: Bacterial Signaling In the Premature Host Leads To Necmentioning
confidence: 86%
“…It is noteworthy that the clinical factors most often seen in association with NEC, including hypoxia, remote infection, and prematurity, are all associated with induced TLR4 expression in the intestine, suggesting a biologic explanation for these clinical observations. The principal findings that the LPS recognition molecule TLR4 is elevated in experimental and human NEC, and that it plays a key role in the pathogenesis of this disease, has been confirmed by a variety of investigators 40,41,42,43,44,45 .…”
Section: Bacterial Signaling In the Premature Host Leads To Necmentioning
confidence: 86%
“…In this regard, it has been established that the development of NEC requires activation of the lipopolysaccharide receptor – namely T oll- l ike r eceptor 4 (TLR4) – on the lining of the intestinal epithelium(8, 14, 15). Genetic or pharmacologic inhibition of TLR4 prevents NEC in mice (13, 1619), and the expression of TLR4 in the intestinal epithelium is higher in the premature as compared with the full-term mouse and human infant (11, 15), explaining in part the reasons for which the premature infant is at risk for NEC development. Further, we recently described that TLR4 plays a critical role in the regulation of epithelial differentiation via effects on Notch signaling in the intestinal stem cells (8), providing insights as to why TLR4 is higher in the premature developing gut as compared with the full term gut.…”
Section: Introductionmentioning
confidence: 99%
“…Saka et al established the protective effect of SP-D in the devastating neonatal intestinal disease, necrotizing enterocolitis (NEC), by establishing that SP-D could attenuate TLR-4 over-expression in immature embryonal intestine cells (Saka et al, 2016). Furthermore, human purified SP-A, given orally to mice in an experimental model of neonatal NEC, reduced intestinal levels of pro-inflammatory cytokines and TLR-4 proteins ameliorating adverse outcomes associated with this often fatal clinical condition (Quintanilla et al, 2015). These results give further credence to the idea that modulation of these surfactant proteins has the potential to be used as targeted therapies in a variety of pathological conditions.…”
Section: Anti-inflammatory Effects Of Surfactant Collectinsmentioning
confidence: 99%
“…More recently, the therapeutic value of SP-A protein was studied in an experimental rat model of neonatal necrotizing enterocolitis (NEC), a potentially fatal infectious/inflammatory pathology of the intestine seen in premature infants (Quintanilla et al, 2015). They found that oral administration of purified human SP-A protein reduced intestinal levels of pro-inflammatory cytokines and TLR-4, as measured by ELISA and western blotting.…”
Section: Review Of the Localization And Known Functions Of Extra-pmentioning
confidence: 99%